Does Tetanus-Diphtheria-Acellular Pertussis Vaccination Interfere with Serodiagnosis of Pertussis Infection? - Pawloski, Lucia C. (American Society for Microbiology, 2012)
An anti-pertussis toxin (PT) IgG enzyme-linked immunosorbent assay (ELISA) was analytically validated for the diagnosis of pertussis at a cutoff of 94 ELISA units (EU)/ml. Little was known about the performance of this ELISA in the diagnosis of adults recently vaccinated with tetanus-diphtheria-acellular pertussis (Tdap) vaccine, which contains PT. The goal of this study was to determine when the assay can be used following Tdap vaccination. A cohort of 102 asymptomatic health care personnel (HCP) vaccinated with Tdap (Adacel; Sanofi Pasteur) were aged 19 to 79 years (median, 47 years) at vaccination. For each HCP, specimens were available for evaluation at 2 to 10 time points (prevaccination to 24 months postvaccination), and geometric mean concentrations (GMC) for the cohort were calculated at each time point. Among 97 HCP who responded to vaccination, a mixed-model analysis with prediction and tolerance intervals was performed to estimate the time at which serodiagnosis can be used following vaccination. The GMCs were 8, 21, and 9 EU/ml at prevaccination and 4 and 12 months postvaccination, respectively. Eight (8%) of the 102 HCP reached antibody titers of ≥94 EU/ml during their peak response, but none had these titers by 6 months postvaccination. The calculated prediction and tolerance intervals were <94 EU/ml by 45 and 75 days postvaccination, respectively. Tdap vaccination 6 months prior to testing did not confound result interpretation. This seroassay remains a valuable diagnostic tool for adult pertussis.